BCL-2 Family protein expression in initial and recurrent glioblastomas: modulation by radiochemotherapy. Issue 6 (1st December 1999) - Strik, H; Deininger, M; Streffer, J; Grote, E; Wickboldt, J; Dichgans, J; Weller, M; Meyermann, R
Abstract : OBJECTIVE: In vitro studies indicate a role of apoptosis regulatory proteins of the BCL-2 family in the resistance of glioblastoma multiforme to irradiation and chemotherapy. To date, no study has compared the expression of these proteins in initial and recurrent tumours. The differences of expression of BCL-2, BCL-X, BAX, and MCL-1 proteins of paired first resection and recurrence glioblastoma specimens were examined. METHODS: Immunohistochemistry was performed in 37 cases of glioblastoma multiforme with paraffin embedded tissue from first resections and their recurrences in three treatment groups (15 radiochemotherapy, 15 irradiation, seven untreated). Ten high power fields were evaluated with an arbitrary score (< 5%=1, 5–50%=2, >50%=3), and cumulative scores for each antigen calculated. RESULTS: In the whole group, we found a significant up regulation of antiapoptotic BCL-2 (median cumulative score of 15 in the primary, 19 at recurrence; p<0.0001 in the Wilcoxon test), BCLX (median scores 20 and 25, respectively, p<0.0001), and MCL-1 (median scores 11 and 14, p=0.0395), and a significant down regulation of proapoptotic BAX (median scores 14 and 11, p<0.0001). In the subgroups, these trends were also found. No association between protein expression and treatment regimen was found, although significant changes were restricted to the subgroups that received adjuvant chemotherapy. No significant correlation with clinical prognosis was detected with the Kaplan-Meier method. CONCLUSIONS: In the development from initial to recurrent glioblastoma multiforme, the BCL-2 family rheostat shifts towards antiapoptotic adjustment in vivo. Importantly, the changes in BCL-2 family protein expression characterised here were also seen in the subgroup of patients who did not receive adjuvant radiotherapy or chemotherapy, suggesting that the changes of BCL-2 family protein expression result not only from radiochemotherapy but also reflect the natural course of disease.